Thai nurses' perceptions and practices of family-centered care: The implementation gap - Tassanee Prasopkittikun; Arunrat Srichantaranit; Sirisopa Chunyasing (Elsevier, 2020)
Objectives: This study was conducted to examine the differences between perceptions and practices of family-centered care among Thai pediatric nurses. Methods: This mixed-methods study consisted of two phases. In the first phase, a descriptive comparative design using the Family-Centered Care Questionnaire - Revised (FCCQ-R) was administered to 142 pediatric nurses from a university hospital in Bangkok, Thailand. In the second phase, qualitative interviews were conducted with 16 pediatric nurses to gather complementary information regarding the major findings from the first phase. Results: The results revealed that family strengths and individuality were rated the highest as the most important elements and the most frequent practices. Parent/professional collaboration was perceived as the least important element, while the design of the heath care delivery system was rated as the least frequent practice. The qualitative data revealed that the major reasons for suboptimal implementation included a common perception that family-centered care is a Western concept, nurses' weak attitudes towards their roles, and a shortage of nurses. Conclusions: Nurses agreed that the identified elements of family-centered care were necessary but that they did not incorporate the concepts into their daily nursing practice to maintain their endorsement of the family-centered care model. Further study is needed to explore how family-centered care is understood and operationalized by Thai nurses and how hospital administration and environments can be modified to support this care model. Keywords: Cognition, Family-centered care, Hospitals, Nurses, Pediatric, Thailand